2015
DOI: 10.1016/j.jmb.2014.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Two-Ball Structure of the Flagellar Hook-Length Control Protein FliK as Revealed by High-Speed Atomic Force Microscopy

Abstract: The bacterial flagellar hook is a short and uniquely curved tube that connects the basal body to the filament. Hook length is controlled at 55 nm on average by a soluble protein FliK in Salmonella enterica serovar Typhimurium. The N-terminal segment of FliK responsible for measuring the hook length is considered to be intrinsically disordered. Here, we show by high-speed atomic force microscopy that a FliK molecule in solution takes on a shape of two balls linked by a flexible string; the larger ball correspon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 32 publications
0
20
0
Order By: Relevance
“…Interestingly, FliK C decreases its volume as the distance between FliK N and FliK C increases whereas the volume of FliK N does not change at all. This suggests that the N‐terminal portion of the FliK T3S4 domain is less stable and tends to become unstructured (Kodera et al ., ). Since helix α1 and strand β1 are not directly involved in the substrate specificity switch (Minamino et al ., ), we propose that conformational rearrangements of the N‐terminal potion of FliK T3S4 may allow Val‐302 and Ile‐304 to be exposed to the solvent, thereby promoting the interaction between the hydrophobic core domain of FliK T3S4 and FlhB CC .…”
Section: Discussionmentioning
confidence: 97%
“…Interestingly, FliK C decreases its volume as the distance between FliK N and FliK C increases whereas the volume of FliK N does not change at all. This suggests that the N‐terminal portion of the FliK T3S4 domain is less stable and tends to become unstructured (Kodera et al ., ). Since helix α1 and strand β1 are not directly involved in the substrate specificity switch (Minamino et al ., ), we propose that conformational rearrangements of the N‐terminal potion of FliK T3S4 may allow Val‐302 and Ile‐304 to be exposed to the solvent, thereby promoting the interaction between the hydrophobic core domain of FliK T3S4 and FlhB CC .…”
Section: Discussionmentioning
confidence: 97%
“…An alignment of these FliK proteins revealed a low similarity between these proteins (data not shown); this result was not unexpected since it has been observed that FliK proteins show a low similarity degree, even in closely related species (36). This low similarity is more pronounced in the N-terminal region, which has been suggested to have an intrinsically disordered structure (37,38).…”
Section: Am1 Cells Display Severalmentioning
confidence: 59%
“…That is, FliK C always interacted with the secretion gate when the hook was longer than 55 nm. We concluded that FliK uses the minimal length as a signal to switch secretion modes but does not measure hook length per se (17). In other words, FliK acts to prevent hook polymerization beyond an optimal functional length (55 nm).…”
mentioning
confidence: 90%
“…In other words, FliK acts to prevent hook polymerization beyond an optimal functional length (55 nm). High-speed atomic force microscopy revealed that the molecular shape of intact FliK in solution was composed of two folded domains of differing sizes, linked by a flexible linker (17). The larger domain corresponded to FliK N , and the smaller domain corresponded to FliK C .…”
mentioning
confidence: 99%
See 1 more Smart Citation